2020
DOI: 10.1080/2090598x.2020.1716294
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of anastomotic urethroplasty in traumatic stricture (distraction defect) of posterior urethra in boys

Abstract: Objective To report the outcomes of operative management of traumatic posterior urethral distraction defect in boys at our Centre, as traumatic posterior urethral stricture in children is a rare condition that presents a major surgical challenge to the paediatric urologist and consensus on the optimal treatment of these strictures in children has not been reached. Patients and methods We retrospectively analysed our data from July 2013 to June 2018. All boys aged ≤16 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Waterloos et al [19] supported trans-perineal urethroplasty for such strictures. Recently, Zafar et al [20] have also reported good results with trans-perineal anastomotic urethroplasty in 38 boys with success rate of 81.5%.…”
Section: Discussionmentioning
confidence: 94%
“…Waterloos et al [19] supported trans-perineal urethroplasty for such strictures. Recently, Zafar et al [20] have also reported good results with trans-perineal anastomotic urethroplasty in 38 boys with success rate of 81.5%.…”
Section: Discussionmentioning
confidence: 94%